Production of low-background CuSn6-bronze for the CRESST dark-matter-search experiment. - Majorovits, B; Kader, H; Kraus, H; Lossin, A; Pantic, E; Petricca, F; Proebst, F; Seidel, W (2009)
One of the most intriguing open questions in modern particle physics is the nature of the dark matter in our universe. As hypothetical weakly interacting massive particles (WIMPs) do interact with ordinary matter extremely rarely, their observation requires a very low-background detector environment regarding radioactivity as well as an advanced detector technique that allows for active discrimination of the still present radioactive contaminations. The CRESST experiment uses detectors operating at milli-Kelvin temperature. Energy deposition in the detectors is recorded via the simultaneous measurement of a phonon-mediated signal and scintillation emitted by the CaWO(4) crystal targets. The entire setup is made of carefully selected materials. In this note we report on the development of ultra-pure bronze (CuSn(6)) wire in small quantities for springs and clamps that are currently being used in the CRESST II setup.